ANALYSIS OF THE ROLE OF DIVIDEND POLICY AS A MEDIATEER OF INVESTMENT OPPORTUNITY SET AND LEVERAGE INFLUENCES ON COMPANY VALUES - RR. Prima Dita Hapsari; Weri Aprilia (Journal Civics And Social Studies, 2023)
This study aims to determine the role of the DPR as a Mediation Variable on the Effect of IOS and DER on Firm Value. Measuring instrument method using purposive sampling. Statistical analysis using SPSS 25 program. The results showed the effect of direct effect partially IOS effect on firm value, DER affects firm value with sig value 0.000. The effect of the indirect effect partially IOS has an effect on the DPR, DER has an effect on the DPR with a sig value 0.000. Test the effect of indirect effect DPR has no effect on the value of the company with a value of sig. 0.523. The value of the coefficient of the effect of the indirect effect is 1.329 < 1.349, the value of the coefficient of the effect of the direct effect, which means that the DPR has an effect as a Mediation variable between the IOS on firm value. The value of the coefficient of the effect of the indirect effect is 0.328 < 0.538, the value of the coefficient of the effect of the direct effect, which means that the DPR has an effect as a Mediation variable between the DER to firm value.